The wound healing effect of four types of beta-glucan - Seo, Gayoung; Hyun, Changlim; Choi, Seungin; Kim, Young Mee; Cho, Moonjae (Applied biological chemistry, 2019)
Beta-glucans, which existed in the cell walls of cereals, bacteria, and fungi, comprise a group of β- d -glucose polysaccharides. We investigated the effects of four kinds of beta-glucan, that are derived from barley, yeast, mushroom, and euglena on wound healing. The migration and viability of keratinocyte or fibroblast were analyzed using the in vitro scratch wound healing assay, invasion assay, MTT assay, and in vivo assay. All the beta-glucans had a significant effect on keratinocyte migration at 20 μM and showed no toxicity on dermal fibroblast. Moreover, treatment of keratinocytes with the beta-glucan derived from the mushroom ( Schizophyllum commune ) promoted in vivo wound closure. The Integrin/FAK/Src pathway is known to affect cell migration by forming lamellipodia. Beta-glucan from S. commune activates the Integrin/FAK/Src signaling pathway in a time-dependent. Reactive oxygen species are associated with fibroblast differentiation to contract dermal layer and synthesize collagens. We found that fibroblast was activated by increasing NOX4 expression. We propose that beta-glucan derived from mushroom is capable of promoting keratinocyte migration via the induction of FAK/Src phosphorylation there by accelerating wound closure and activating dermal fibroblast differentiation through NADPH oxidase for matrix remodeling.